Potential Role and Excretion Level of Urinary Transferrin, KIM-1, RBP, MCP-1 and NGAL Markers in Diabetic Nephropathy - Siddiqui K (Dove Medical Press, 2020)
Khalid Siddiqui,1 Salini Scaria Joy,1 Teena Puthiyaparampil George,1 Muhammad Mujammami,1– 3 Assim A Alfadda1,3,4 1Strategic Center for Diabetes Research, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2University Diabetes Center, King Saud University Medical City, King Saud University, Riyadh, Saudi Arabia; 3Department of Medicine, College of Medicine, and King Saud University Medical City, King Saud University, Riyadh, Saudi Arabia; 4Obesity Research Center, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Khalid SiddiquiStrategic Center for Diabetes Research, College of Medicine, King Saud University, P.O. Box 245, Riyadh 11411, Kingdom of Saudi ArabiaTel +966 114724179 ext.1340Email ksiddiqui@ksu.edu.saBackground: Analyzing urinary biomarkers may provide better insight into pathophysiological mechanisms of diabetic kidney diseases. The study aimed to analyze the pattern of selected excreted urinary biomarkers and its correlation with albuminuria and estimated glomerular filtration rate (eGFR) in patients with type 2 diabetes.Methods: A total of 185 patients with type 2 diabetes were categorized according to KDIGO guideline based on albuminuria and eGFR. The urinary markers (transferrin, KIM-1, RBP, MCP-1 and NGAL) were measured by ELISA.Results: The urinary markers were associated with eGFR (total protein/Cr, p=0.001; RBP/Cr, p=0.007; MCP-1/Cr, p=0.023; NGAL/Cr, p=0.011) and albuminuria (total protein/Cr, p< 0.001; transferrin, p< 0.001; RBP/Cr, p< 0.001; MCP-1/Cr, p< 0.001; NGAL/Cr, p=0.002).Conclusion: The urinary marker levels (total protein, RBP, MCP-1, and NGAL) are elevated with severity of kidney damage and expressed more in progressive renal impairment.Keywords: diabetic kidney disease, urinary markers, albuminuria, transferrin, kidney injury molecule-1, retinol-binding protein, monocyte chemoattractant protein-1, neutrophil gelatinase-associated lipocalin